Reconfiguring Islamic Education in the Age of Artificial Intelligence: A Bibliometric Mapping for Future Research Directions - Sholahudin, Tammam; Alifah, Dhiva Noer; Ghazali, Nurul Nasrin Zahirah binti; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2025)
This study explores the development and thematic structure of research on Artificial Intelligence (AI) in Islamic education using a bibliometric approach. A total of 234 English-language journal articles indexed in Scopus between 2010 and 2025 were analyzed using a focused keyword strategy combining “Islamic Education” and “Artificial Intelligence.” Bibliometric indicators and visualization techniques were employed to examine publication trends, influential contributors, and thematic patterns. The findings reveal a rapid growth of publications since 2022, with research output dominated by Indonesia and Malaysia. The thematic analysis shows that AI related technological themes occupy a central position, while Islamic educational ethics, epistemology, and institutional dimensions remain marginal. This indicates that AI is largely treated as an instrumental tool rather than a transformative force within Islamic education. The study highlights the need for future research to integrate AI development with the philosophical, ethical, and spiritual foundations of Islamic education.